Nurses' Wisdom in Action in the Emergency Department - Susan A. Matney; Nancy Staggers; Lauren Clark (SAGE Publishing, 2016)
Nurses seek to understand better what practicing with wisdom means and how to apply wisdom to practice; however, the experience of wisdom in nursing has not been well defined or researched. This study was designed to understand how emergency department (ED) nurses construct the meaning of wisdom within the culture of clinical nursing practice. Using Charmaz's constructivist grounded theory methodology, we developed a preliminary theory capturing the experience of wisdom in practice. The core theoretical model focuses on two juxtaposed processes, technical and affective, and is grounded in expertise. Significant findings were the recognition of affective categories, such as emotional intelligence, required to practice using wisdom. Results reinforce and extend the current wisdom literature and provide a new perspective on wisdom in practice in a nursing context.